Pengaruh Konten Pemasaran dan Kualitas Produk Terhadap Minat Beli Konsuemen pada Suku Cadang Otomotif Di E-Commerce - Agustin, Imel Aura; Zahrah, Halimah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of marketing content and product quality on consumers’ purchase intention of automotive spare parts in e-commerce. The rapid development of e-commerce and social media platforms, particularly TikTok, has significantly influenced consumer behavior in searching for information and making purchase decisions. However, the decline in sales performance, reduced effectiveness of marketing content, and consumer complaints regarding product quality indicate a decrease in purchase intention. This research employs a quantitative approach using a survey method. The sampling technique used was convenience sampling with 60 respondents who were followers of PT XYZ’s TikTok account and met the research criteria. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with SPSS version 27. The results show that marketing content has a positive and significant effect on purchase intention. Product quality also has a positive and significant effect on purchase intention, with a more dominant influence compared to marketing content. Simultaneously, marketing content and product quality have a significant effect on consumers’purchase intention. These findings suggest that improving informative and engaging marketing content, along with maintaining consistent product quality, can enhance consumer trust and increase purchase intention in automotive spare parts e-commerce.